2019
DOI: 10.1017/jfm.2019.286
|View full text |Cite
|
Sign up to set email alerts
|

Penetrative turbulent Rayleigh–Bénard convection in two and three dimensions

Abstract: Penetrative turbulent Rayleigh-Bénard convection which depends on the density maximum of water near 4 • C is studied using two-dimensional (2D) and three-dimensional (3D) direct numerical simulations (DNS). The working fluid is water near 4 • C with Prandtl number P r = 11.57. The considered Rayleigh numbers Ra range from 10 7 to 10 10 . The density inversion parameter θ m varies from 0 to 0.9. It is found that the ratio of the top and bottom thermal boundary-layer thickness (F λ = λ θ t /λ θ b ) increases wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 49 publications
6
40
1
Order By: Relevance
“…For zonal flow γ Nu is much smaller, namely only 0.17. The effective scaling exponent γ Re in Re ∼ Ra γ Re is approximately 0.6 for zonal flow and approximately 0.67 for the convection roll state, which is also close to the GL predication of 2/3 for the I < ∞ and III ∞ regimes (Grossmann & Lohse 2001;Shishkina et al 2017) for no-slip cases, while it is larger than 0.6 that has been reported for 2-D RB convection with no-slip plates (Sugiyama et al 2009;Zhang et al 2017;Wang et al 2019c).…”
Section: Nusselt Number and Reynolds Numbersupporting
confidence: 85%
See 3 more Smart Citations
“…For zonal flow γ Nu is much smaller, namely only 0.17. The effective scaling exponent γ Re in Re ∼ Ra γ Re is approximately 0.6 for zonal flow and approximately 0.67 for the convection roll state, which is also close to the GL predication of 2/3 for the I < ∞ and III ∞ regimes (Grossmann & Lohse 2001;Shishkina et al 2017) for no-slip cases, while it is larger than 0.6 that has been reported for 2-D RB convection with no-slip plates (Sugiyama et al 2009;Zhang et al 2017;Wang et al 2019c).…”
Section: Nusselt Number and Reynolds Numbersupporting
confidence: 85%
“…For the 2-D horizontally periodic cases with no-slip plates, Nu ∼ Ra 0.29 is found with Pr = 1, Ra ≤ 10 10 (Johnston & Doering 2009;Zhu et al 2018a). For 2-D RB convection with no-slip plates and sidewalls with unit aspect ratio, several studies have shown that Nu ∼ Ra 0.3 and Re ∼ Ra 0.6 (Sugiyama et al 2009;Zhang, Zhou & Sun 2017;Wang et al 2019c). However, how these effective scaling relations will change for free-slip plates has not been Figure 8(a) reveals that the heat transfer in the convection roll state is much higher than that of the zonal flow state.…”
Section: Nusselt Number and Reynolds Numbermentioning
confidence: 96%
See 2 more Smart Citations
“…As a result, the fluid self organizes into a well-mixed convective layer adjacent to a stably stratified layer. The use of a nonlinear equation of state with a density maximum is motivated by the similar behavior of water near its density maximum of 4 • C [37][38][39] and allows to study the coupled dynamics of two-layer mixed turbulent and stably stratified geophysical and astrophysical fluids. Here, β(T ) is piecewise-constant and is positive for T T inv = 0 and negative for T < T inv = 0 (i.e., we use T inv as reference temperature).…”
Section: Problem Formulationmentioning
confidence: 99%